Food intake challenges and coping mechanisms faced by university students in Quezon city, Philippines during the first 6 months of the COVID-19 pandemic. - Arizo, Pearl Merguerette C.; Balalio, Trisia mae F.; Elogada, Eryka S. (College of Home Economics, University of the Philippines Diliman, 2023)
The COVID-19 pandemic, along with its subsequent intervention measures impacted the food system in the country. This study aimed to explore the challenges and coping mechanisms on food intake faced by university students in Quezon City, Philippines during the first six months of the COVID-19 pandemic. A phenomenological research design was employed, using purposive and snowball sampling to recruit six participants from Higher Education Institutions (HEIs) in Quezon City. Through semi-structured interviews, participants' demographic characteristics, experiences with food intake challenges, and coping mechanisms were collected and then analyzed using thematic analysis. Findings showed that quarantine regulations disrupted the food system, limiting students' access to food sources. Financial constraints, loss of income, and rising food prices further exacerbated the difficulties in obtaining sufficient food. The reliance on processed foods provided through relief efforts resulted in a lack of food variety. Additionally, the unavailability and inaccessibility of fresh fruits and vegetables contributed to limited dietary diversity. Participants adapted their purchasing habits by shifting to online platforms, reducing the amount purchased, and bulk buying. They also modified their eating habits, including preparing meals, choosing high satiety foods, reducing meal/portion size, reducing snacking, and adjusting eating patterns. These findings highlight the need to address food-related challenges and provide adequate support to students ensuring the availability, accessibility, and affordability of food during a global health crisis.